Answer:
4
Step-by-step explanation:
4^(1/2a)/2^b
[tex]\frac{4^{\frac{1}{2} a} }{2^b}\\=\frac{(2^{2})^{\frac{1}{2}a} }{2^b}\\=\frac{2^{2 \times \frac{1}{2}a } }{2^b} \\=\frac{2^a}{2^b} \\=2^{a-b} \\=2^2\\=4[/tex]
A playground is 224 square feet. How many square inches is that?
Answer:
32256 square inches
Step-by-step explanation:
Formula
multiply the area value by 144
ACTIVITY 1:
1. 10. A fish-tank has a length of 45 centimeters, a width of 25 centimeter, and a depth of 10
centimeter. Find the volume of the fish-tank.
As part of a competition Diego must spin around in a circle six times and then run to a tree. The time he spends on each spin is represented by s and the time he spends running is r. He gets to the tree 21 seconds after he starts spinning. Write an equation showing the relationship between s and r.
Answer:
6s + 2r = 21
Step-by-step explanation:
Please kindly see the attached file for explanaion
The correct equation showing the relationship between s and r is 6s + r = 21
To derive this equation, we consider the total time Diego spends on the competition, which is the sum of the time he spends spinning and the time he spends running.
Since Diego spins around in a circle six times and each spin takes time s, the total time spent spinning is 6s
After spinning, he runs to the tree, which takes time r.
Therefore, the total time from the start of the spinning until Diego reaches the tree is the sum of the time spent spinning and running.
Given that Diego reaches the tree 21 seconds after he starts spinning, we can set up the following equation to represent this relationship:
6s + r = 21
This equation states that six times the time spent on each spin plus the time spent running equals 21 seconds.
Solving this equation for either s or r would give us the time spent on each activity, provided we know the total time of 21 seconds.
Factor the following polynomial:
5x(a-b)-2y(a-b)
Answer:
(a - b)(5x - 2y)
Step-by-step explanation:
Given
5x(a - b) - 2y(a - b) ← factor out (a - b) from each term
= (a - b)(5x - 2y) ← in factored form
The polynomial 5x(a-b)-2y(a-b) can be factored into (a-b)(5x-2y). This is achieved by taking out the common factor of (a-b) from both terms.
Explanation:To factor the polynomial
5x(a-b)-2y(a-b)
, you first notice that the terms have a common factor, (a-b). Factoring is a process where you write the expression as a product of its factors. In this case, you can pull out the common factor from both terms. This leaves you with
(a-b)(5x-2y)
. So, the factored form of the given polynomial is (a-b)(5x-2y). By applying the distributive property, you can check your work: (a-b)*5x gives the first term and (a-b)*(-2y) gives the second term, confirming the factored form is correct.
Learn more about Factoring Polynomials here:https://brainly.com/question/28315959
#SPJ2
Kathi and Robert Hawn had a pottery stand at the annual Skippack Craft Fair. They sold some of their pottery at the original price of $9.50 each, but later decreased the price of each by
$3.00. If they sold all 95 pieces and took in $707.50, find how many they sold at the original price and how many they sold at the reduced price
The number sold at $9.50 is
The number sold at $6.50 is
Answer:
Amount of potteries sold at $9.50 is 30
And that of $6.50 is 65 potteries
Step-by-step explanation:
Kindly refer to the attached image for explanations
Solve the equation. SHOW your work. SHOW which properties of equality you used to solve each equation.
3( y + 4) = 24
Answer:
y = 4
Step-by-step explanation:
We have to use the distributive property. Remember that the distributive property states that when expanding out a parentheses, you must find the sum of the product of the "outside term" with each of the "inside terms".
In this case, the "outside term" is 3 and the "inside terms" are y and 4. So, we need to multiply 3 by each of y and 4 and then add those together:
3(y + 4) = 24
3 * y + 3 * 4 = 24
3y + 12 = 24
Now, we subtract 12 from both sides to isolate the variable:
3y + 12 - 12 = 24 - 12
3y = 12
Finally, divide by 3 from both sides to get y alone:
3y/3 = 12/3
y = 4
Thus, y = 4.
Hope this helps!
Answer:
y = 4
Step-by-step explanation:
3(y+4) = 24 <- This is a linear equation so its solved as such
3y+12 = 24 <- Distribute the (PEMDAS)
-12 -12 <- Get y alone
3y = 12 <- Rewrite with y alone
[tex]\frac{3y}{3}[/tex] = [tex]\frac{12}{3}[/tex] <- Divide both sides
y = 4
Walter invested $5,000 each in two plans. Plan A pays $280 per year, and plan B pays
5% interest compounded annually.
At the end of which year does the total interest earned under plan B exceed that earned
under plan A for the first time?
a.5th year
b.6th year
c.7th year
d.8th year
A 7-foot roll of red ribbon costs $0.42. What is the unit price?
Answer:
$0.06 per foot
Step-by-step explanation:
You can solve this by dividing 7 from 0.42.
$0.42 ÷ 7 = $0.06
is 3, -3, 3, -3 a geometric sequence
Answer:
Step-by-step explanation:
yes it is a geometric sequence
a1=3
r=-3/3=-1
25 POINTS!!! PLEASE HELP!!!
What is the slope of the line that contains these points?
Answer
-8/2
Step-by-step explanation:
You use substitution to solve a system of equations and, after simplifying the equations, end with an expression that says 0 = 4. What does that say about the the lines and about the number of solutions to the system?
Answer:
Step-by-step explanation:
It means there is no solution and the lines are parallel. It is called an inconsistent system.
I hope this helps
The system has no solution. Thus, the lines are parallel to each other.
The system of the equation has no solution. The expression leads to the value that is 0=4, which means you concluded the final result as 0=4.
Do you think practically it is possible, never, it is not possible to equate zero with four, same in the solutions of the system in the lines, this kind of results will not be taken by the intersecting lines.
Hence, the above expression is the condition for "No Solution"
If we try to evaluate the solution of the system that has no solution or an infinite number of solutions, then the variables are canceled out and only the constant values are left that are not equal.
Therefore, The lines are parallel and the system of the equation has no solution.
To know more about it, please refer to the link:
https://brainly.com/question/2648990
Solve for F
3(6-f)-4=3f-4
Answer: f = 3
Step-by-step explanation:
3(6 - f) - 4 = 3f - 4
(Distribute the 3 on the left side)
18 - 3f - 4 = 3f - 4
(Combine like terms on the left (18 and -4))
14 - 3f = 3f - 4
(add 3f to both sides)
14 = 6f - 4
(Add 4 to both sides)
18 = 6f
(Divide by 6 on both sides)
3 = f
quick help , i don’t know how to do this . can you help me please ? 20 points
Answer:
a) (3a² + 1) - (4 + 2a²) =
3a² + 1 - 4 - 2a² =
a² - 3
b) (5p² - 3) + (2p² - 3p³) =
5p² - 3 + 2p² - 3p³ =
-3p³ + 7p² - 3
c) (5a + 4) - (5a + 3) =
5a + 4 - 5a - 3 = 1
d) (9r³ + 5r² + 11r) + (-2r³ + 9r - 8r²) =
9r³ + 5r² + 11r - 2r³ + 9r - 8r² =
7r³ - 3r² + 20r
Use the graph to write a linear function that relates y to x
Answer:
y = 3
Step-by-step explanation:
This is a constant function
y = 3
The equation of a line can be predicted easily if two points are given. Thus, the equation of the required line is [tex]\bold{y=4}[/tex].
We need to determine the equation of the line with the help of the given graph.
Now, take two points from the graph. The points are ( 1, 4 ) and ( 2, 4 ).
The if a line passed through the two points say [tex](x_1,y_1)\;\rm{and}\;(x_2,y_2)[/tex], then the equation of the line can be formulated as:
[tex](y-y_1)=\dfrac{y_2-y_1}{x_2-x_1}(x-x_1)[/tex]
Therefore, apply the formula and solve it further.
[tex]\begin{aligned} (y-4)&=\dfrac{4-4}{3-2}(x-1)\\y-4&=0\\y&=4 \end{aligned}[/tex]
Thus, the equation of the line is [tex]\bold{y=4}[/tex]
To know more about the equation of the line, please refer to the link:
https://brainly.com/question/20632687
(This is multiplication) Kim bought 1.5 pounds of American cheese that cost $4.50 per pound. She also bought 1.75 pounds of Swiss cheese that cost $4.80 per pound.
How much did Kim spend in all?
$9.30
$11.55
$15.15
$21.60
Answer:
15.15
Step-by-step explanation:
Answer:
15.15
i worked it out on paper
F(x)=-x^2 -4x -2, for this equation find the solutions, the coordinates of the vertex, and the axis of the symmetry.
Answer:
Step-by-step explanation:
hello :
Completing The Square x²-4x-2= (x²-4x+4)-4-2 = (x-2)²-6
the vertex is : (2 , -6)
now calculate the solutions : (x-2)²-6 =0
(x-2)²= 6 means : x-2 =√6 or x-2 = -√6
x = 2+√6 or x = 2-√6
Select all of the expressions which correctly show how to convert 18 inches into yards.
18 in. ⨉ 1yd36in.
18 in. ⨉ 36 yd
18 in. ⨉ 36in.1yd
18 in. ⨉ 1yd12in.
18 in. ⨉ 1ft12in. ⨉ 1yd3ft
Answer:
All correct ones:
18in. x 36in. 1yrd.
18in. x 1ft 12in. x 1yrd 3ft
Step-by-step explanation:
The correct expressions to convert 18 inches into yards are:
18 in ⨉ 1yd/36 in. Thus, option a is correct.
What is the Measurement Conversion?Measurement conversion refers to the process of changing a quantity from one unit of measurement to another unit of measurement.
The first expression uses the conversion factor of 1 inch = 1/36 yards
Then, 18 inches = 18 × 1/36 yards
or,
18 in ⨉ 1yd/36 in
The correct expressions to convert 18 inches into yards are:
18 in ⨉ 1yd/36 in. Thus, option a is correct.
To learn more about Measurement Conversion, Visit
https://brainly.com/question/174910
#SPJ1
Complete question:
3 divided by9 draw a picture that show the division expression
Answer:
1/3
Step-by-step explanation:
3/9 = 1/3
An 18-foot long ramp is placed at a loading
dock that is 5 feet above ground. How far is
the bottom of the ramp from the dock?
solve 5+x/2=16. show your work please
Answer:
Download photomath it's really helpful
Which net represents this solid figure?
Answer:
The correct net is attached.
What is the measure of ∠A, to the nearest degree?
17°
33°
57°
73°
Answer:
73
Step-by-step explanation:
this is the answer bc it is near a 90 degree angle but not there yet but close
Mrs. Rodriguez has 63 packages of pens in stock at her store on Monday. On Tuesday, she has 7/9 the number of pens she had on Monday. On Wednesday, she has 1/7 of the number of pens she had on Tuesday. How many packages of pens does she have on Wednesday
Answer:
7 packages
Step-by-step explanation:
Tuesday:
To work this out you would first need to work out how many she has on Monday. First you would divide 63 by 9 to work out 1 ninth, which gives you 7. Then you would multiply 7 by 7 to work out 7 ninths, which gives you 49.
1) Divide 63 by 9.
[tex]63/9=7[/tex]
2) Multiply 7 by 7.
[tex]7*7=49[/tex]
3) She has 49 packages on Tuesday
Wednesday:
To work this out for Wednesday you would first divide 49 by 7 to work out what one seventh is, Which gives you 7. Then you would multiply 7 by 1, which gives you 7.
1) Divide 49 by 7.
[tex]49/7=7[/tex]
2) Multiply 7 by 1.
[tex]7*1=7[/tex]
3) She has 7 packages on Wednesday
solve for x. log10x=4
Final answer:
To solve the equation log10x = 4, we convert it to its exponential form, which is 10^4 = x. By doing the calculation, we find that x equals 10,000. This value is the inverse log of the number 4.
Explanation:
To solve the equation log10x=4, we need to understand that this is a common logarithmic equation where the base of the logarithm is 10. The equation essentially asks what power we must raise 10 to in order to get x. In this case, the power is 4.
According to the properties of logarithms, we can rewrite the equation in its exponential form which is 10^4 = x. So, x = 10,000.
This value of x is obtained by taking the inverse log of 4 or calculating 10^4 using a calculator, which yields the result 10,000. Therefore, x = 10,000 is the solution to the equation log10x = 4.
To go to a movie, a family with 2 adults and 4 children spends $64. A family containing 1 adult and 3 children spends $42. Find the cost of an adult movie ticket and the cost of a child movie ticket.
Answer:
all work is pictured and shown
The cost of a ticket for an adult is $12 while for children it is $10.
How to form an equation?Determine the known quantities and designate the unknown quantity as a variable while trying to set up or construct a linear equation to fit a real-world application.
Let's assume that cost for adults is A while for children it is C
Now,
2 adults and 4 children spend $64.
2A + 4C = 64
1 adult and 3 children spend $42.
A + 3C = 42
Multiply by 2
2A + 6C = 84
By subtracting equations
6C - 4C = 84 - 64
2C = 20
C = 10
A = 42 - 3(10)
A = 12
Hence "The cost of a ticket for an adult is $12 while for children it is $10".
For more about the equation,
https://brainly.com/question/10413253
#SPJ2
If the risk-free rate is 8 percent and the market risk premium is 2 percent, what is the required return for the market?
The required return for the market can be calculated using the Capital Asset Pricing Model (CAPM), which takes into account the risk-free rate, beta value, and market risk premium.
Explanation:The required return for the market can be calculated using the Capital Asset Pricing Model (CAPM). The CAPM formula is:
Required Return = Risk-Free Rate + Beta * Market Risk Premium
In this case, the risk-free rate is given as 8%, and the market risk premium is given as 2%. To calculate the required return for the market, we need to know the beta value, which represents the stock's sensitivity to market movements.
Once we have the beta value, we can substitute it into the formula to find the required return for the market.
Final answer:
The required return for the market, when the risk-free rate is 8 percent and the market risk premium is 2 percent, is 10 percent according to the Capital Asset Pricing Model.
Explanation:
The student is inquiring about the concept of the required return of the market, which is a fundamental concept in finance related to the Capital Asset Pricing Model (CAPM). According to CAPM, the required return on a market portfolio (the market) is the sum of the risk-free rate and the market risk premium. In this case, with an 8 percent risk-free rate and a 2 percent market risk premium, the required return for the market would be the sum of these two figures, which equals 10 percent.
Find the sum: 4 radical 3 + 11 radical 12
Answer:
[tex]26\sqrt{3}[/tex]
Step-by-step explanation:
We want to find [tex]4\sqrt{3} +11\sqrt{12}[/tex]. [tex]11\sqrt{12}[/tex] can be written as [tex]11\sqrt{4*3}=11*\sqrt{4} *\sqrt{3}=11*2*\sqrt{3}=22\sqrt{3}[/tex], so we can now write our original equation as: [tex]4\sqrt{3}+22\sqrt{3}[/tex].
We can combine like terms: [tex]4\sqrt{3}+22\sqrt{3}=26\sqrt{3}[/tex]
Hope this helps!
Answer:
17 radical 3
Step-by-step explanation:
4(rad)3+11(rad)12
factor 12 into 13(rad)3
add 11 and 13 now that they have the same radical
keep inside rad of 3 and put 17 on the outside bc 4+13...
Find length of PR. TR=x+11
Step-by-step explanation:
In a square,
we know that when diagonals bisect each other it is divided into two equal parts
so
TR = TP
So
PR = x +11 + x + 11
= 2x + 22
And
Both diagonals are equal so
QS = PR
7x - 3 = 2x + 22
7x - 2x = 22 + 3
5x = 25
x= 25 /5
x = 5
Now
PR = 2 * 5 +22= 10 +22 = 32
Answer:
PR = 34
Step-by-step explanation:
The diagonals of a square bisect each other, and are congruent, thus
QS = PR, that is
7x - 8 = x + 11 + x + 11 = 2x + 22 ( subtract 2x from both sides )
5x - 8 = 22 ( add 8 to both sides )
5x = 30 ( divide both sides by 5 )
x = 6
Thus
PR = 2x + 22 = 2(6) + 22 = 12 + 22 = 34
A cylinder and its dimensions are shown below.
12.1 cm
3.8 cm
One equation for calculating the volume of a cylinder is V=Bh, where 8 represents the area of the base of the cylinder. Which expression can be used to find the value of B, in square centimeters, for this cylinder?
A (12.1 B 2(12.1)
C (3.8)
D None of these
Answer:
[tex](A) B=\pi (12.1)^2[/tex]
Step-by-step explanation:
Given a cylinder with the following dimensions
Radius of the Cylinder =12.1 cm
Height of the Cylinder =3.8cm
Volume of a cylinder = Base Area X Height
The base area is a circle, therefore the expression that can be used to find the value of B, (in square centimeters), for this cylinder is given as:
[tex]Base Area =\pi r^2\\B=\pi (12.1)^2[/tex]
The correct option is A. (12.1) expression can be used to find the value of B, in square centimeters, for this cylinder.
To find the value of B, which represents the area of the base of the cylinder, we can use the formula for the volume of a cylinder, V = Bh, where V is the volume, B is the area of the base, and h is the height.
We are given the volume V = 12.1 cm³ and the height h = 8 cm.
We can rearrange the formula to solve for B:
[tex]\[ B = \frac{V}{h} \][/tex]
Substituting the given values:
[tex]\[ B = 1.5125 \text{ cm}^2 \][/tex]
Since the volume and height are both given in centimeters, the unit for B will be in square centimeters.
The expression that can be used to find the value of B is indeed the volume divided by the height, which simplifies to the given volume of 12.1 cm³ divided by the height of 8 cm, resulting in [tex]\( B = \frac{12.1}{8} \) or \( B = 1.5125 \).[/tex]
Therefore, the expression to find the value of B, in square centimeters, for this cylinder is [tex]\( B = \frac{12.1}{8} \),[/tex] which is option A. (12.1).
(10•2) •3 = 10•(2•3)
A. True
B. False
Answer:
True
Step-by-step explanation:
(10 x 2) x 3 = 60
10 x ( 2 x 3) = 60
They are the same. Order doesn't matter for multiplication.
Answer:
True
Step-by-step explanation:
10•2) •3 = 60
&
10•(2•3) = 60
The variables are rearranged, yet without the parentheses the outcome could be faulty.
I hope this was the brainliest answer & helped you better understand!